Empirical research approach of construction waste quantification and standard tolerance for stratified residential building projects / Nur Amierah Harun, Asmalia Che Ahmad and Faridah Ismail - Nur Amierah, Harun; Asmalia, Che Ahmad; Faridah, Ismail (Universiti Teknologi MARA, Perak, 2017)
The construction industry is the major solid waste generator in Malaysia. The extensive building and infrastructure development projects have led to an inclination in construction waste generation. The accurate waste composition and quantity are hardly to be measured, as the construction activity is dynamic in nature. Every construction stage produced different types of waste and amount. Therefore, the pattern of waste generated throughout the construction stages need to be identified. This paper critically reviewed construction waste issue in Malaysia in orderto identify the gap in research. Based on literature studied, this paper proposes an approach to quantify the wastage rate and develop constructionwaste standard tolerance forstratified residential building projects. There are six steps in the empirical research approach. First is identification of the stratified residential construction buildings. Second is characteristics of project analyze issimilarfor uniform investigation. Third is determination of construction stages. Fourth is quantification of the waste generated in the construction projects studied. The fifth step is conduct structure interview with the authorized person. The last step is summation of the recorded quantity and development of construction waste standard tolerance. It is expected that the proposed research approach will be practical for construction waste quantification and for future research undertaken.